Burning modes of a bipolar pulsed discharge in CO₂ - Lisovskiy, V.A.; Dudin, S.V.; Vusyk, M.M.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2020)
We have studied the burning modes of the bipolar pulsed discharge in CO₂ within the frequency range between 20 and 300 kHz and the duty cycle of 11…97%. The current and voltage waveforms within the pressure range between 0.1 to 1 Torr were registered. We have established that the duty cycle values may affect the axial structure of the discharge considerably causing the voltage drop redistribution across the electrodes. The bipolar pulsed discharge may burn in a high-current mode (with cathode sheaths near every electrode) as well as in a low-current one (with a low discharge current and weak glow). The transition between these modes may be observed at high duty cycle values. We have found that one may make a shift of the complete oscilloscope voltage pattern higher or lower along the voltage axis and produce a self-bias constant voltage the value and sign of which depend on the duty cycle, amplitude and frequency of the applied voltage.